2016
DOI: 10.1097/scs.0000000000003129
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrically-Based Surgical Technique for Tessier 3 Cleft Reconstruction

Abstract: Craniofacial clefts are rare entities, with an incidence reported as 1.43 to 4.85 per 100,000 births. The Tessier number 3 cleft, the most medial of the oblique clefts, can manifest as clefting of the lip between the canine and lateral incisors, colobomas of the nasal ala and lower eyelid, and inferior displacement of the medial canthus-frequently disrupting the lacrimal system with extreme variability in expressivity (Eppley).Literature on cleft lip repair is extensive and has evolved to incorporate anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…4 Recently, Morgan and colleagues have suggested that a repair based on anthropometrics of the deformity is needed to mask the stigma of the Tessier 3 cleft; they present a case report to demonstrate this. 5 Still, despite the literature, little is found to help technically guide the surgeon. Hence, we present a step-by-step description to managing these complex patients using principles learned from the anatomical subunit cleft lip repair.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Recently, Morgan and colleagues have suggested that a repair based on anthropometrics of the deformity is needed to mask the stigma of the Tessier 3 cleft; they present a case report to demonstrate this. 5 Still, despite the literature, little is found to help technically guide the surgeon. Hence, we present a step-by-step description to managing these complex patients using principles learned from the anatomical subunit cleft lip repair.…”
Section: Discussionmentioning
confidence: 99%
“…Our series builds off of these previously published concepts. [2][3][4][5] In addition, we have incorporated the use of triangles and opening incisions seen in the anatomical subunit repair of cleft lips. 10 With wide subperiosteal undermining and bilaminar dissection, we postulate that incisions can be closed along anatomic subunits and the use of flaps outside the ones described are not necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations